2019
DOI: 10.1007/s00442-019-04490-1
|View full text |Cite
|
Sign up to set email alerts
|

Invasive knotweed has greater nitrogen-use efficiency than native plants: evidence from a 15N pulse-chasing experiment

Abstract: Habitats with fluctuating resource conditions pose specific challenges to plants, and they often favor a small subset of species that includes exotic invaders. These species must possess a superior ability to capitalize on resource pulses through faster resource uptake or greater resource-use efficiency. We addressed this question in an experiment with invasive knotweed, a noxious invader of temperate ecosystems that is known to benefit from nutrient fluctuations. We used stable isotopes to track the uptake an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 58 publications
(63 reference statements)
2
14
0
Order By: Relevance
“…More than the other species, F. x bohemica was able to produce high aboveground biomass in a nitrate-rich environment, and thus, although its assimilation rate was not significantly different than that of the other species, it was able to accumulate the highest amount of labeled nitrate in NO 3 − rich soil. These results in natural soils are consistent with recent findings [32], who showed that Japanese knotweeds did not have a better nitrogen uptake efficiency than that of native species but had a better nitrogen use efficiency (i.e., the biomass produced due to the uptake of nitrogen). On the other hand, U. dioica showed the highest root biomass, especially in low nitrate soil, and the highest nitrate assimilation rate.…”
Section: Impact Of Knotweed On Competing Species: From Little Negativsupporting
confidence: 92%
“…More than the other species, F. x bohemica was able to produce high aboveground biomass in a nitrate-rich environment, and thus, although its assimilation rate was not significantly different than that of the other species, it was able to accumulate the highest amount of labeled nitrate in NO 3 − rich soil. These results in natural soils are consistent with recent findings [32], who showed that Japanese knotweeds did not have a better nitrogen uptake efficiency than that of native species but had a better nitrogen use efficiency (i.e., the biomass produced due to the uptake of nitrogen). On the other hand, U. dioica showed the highest root biomass, especially in low nitrate soil, and the highest nitrate assimilation rate.…”
Section: Impact Of Knotweed On Competing Species: From Little Negativsupporting
confidence: 92%
“…Allelopathy in Japanese knotweed is thought to be subject to resource allocation and is increased when nutrient supply is high [ 108 ], inhibiting the growth rather than the germination of native species [ 109 ]. This plant species is a known opportunist, which is able to take advantage of the fluctuation in resources associated with riparian areas [ 112 ] using its superior nitrogen-use efficiency compared with native species [ 113 ]. Plasticity is also thought to be resource dependent, with invasive species showing greater phenotypic plasticity than native plants if resources are plentiful [ 35 ].…”
Section: Resultsmentioning
confidence: 99%
“…Separate above ground (leaf and stem) biomass and below ground (root) biomass of each individual. These samples were put into oven at 72 • C for 48 h to measure dry weight of each individual [26]. The relative growth rate of total dry weight (RGR B ), relative growth rate of stem length (RGR SL ), stem weight ratio (SWR), root weight ratio (RWR) and leaf specific area (SLA) were calculated using the following equations shown in Table 1.…”
Section: Growth and Physiological Traits Measurementmentioning
confidence: 99%